Small-Scale Coastal Fishing Shapes the Structure of Shallow Rocky Reef Fish in the Aegean Sea - Sini, Maria; Vatikiotis, Konstantinos; Thanopoulou, Zoi; Katsoupis, Christos; Maina, Irida; Kavadas, Stefanos; Karachle, Paraskevi K.; Katsanevakis, Stelios (Frontiers in Marine Science, 2019)
Shallow rocky reef fish assemblages were studied in sites of low versus high fishing pressure (FP) across different parts of the Aegean Sea, in order to assess community structure at a large scale and investigate spatial variability in relation to FP, depth, and geographic location. A total of 15 pairs of high and low FP sites were selected (18 sites in North Aegean, 12 in South Aegean). The level of FP was defined based on a fishing pressure index specifically developed for coastal small-scale fisheries in the region. In each site, fish communities were investigated at two depth zones (5 and 15 m). Number of species, fish size (TL) and abundance were recorded along strip transects through underwater visual surveys. Abundance and TL were used to estimate biomass, and fish species were assigned to distinct trophic and commercial status groups. An 8-fold range in fish density and a 14-fold range in fish biomass were detected, while community structure was affected by all spatial variables considered (FP, depth, geographic location). The N Aegean sites scored higher in number of species and biomass of carnivorous fish, whereas the S Aegean had a higher biomass of several allochthonous and thermophilous species. Abundance and biomass estimates were higher in low FP sites, and primarily at the 15 m depth zone, where low FP sites had 2 times higher abundance and 2.8 times higher biomass. However, differences were mainly due to an increase of fish with low or no commercial value, whereas biomass of highly-priced fish was overall low. Given that sites of lower FP represent areas of lower conflicting interests for fisheries whilst providing enhanced biomass levels, they should be included in future marine conservation planning schemes, as they could contribute to the replenishment of fisheries and the boosting of conservation benefits provided by MPAs, once properly managed.